KINERJA PROGRAM PEMBERDAYAAN MASYARAKAT DESA DI KECAMATAN BOLANGITAN BARAT KABUPATEN BOLAANG MONGONDOW UTARA - KINONTOA, RIZKY FAIZ; POSUMAH, JOHNNY; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2022)
The purpose of this study is to determine how the performance of the communityempowerment program in the District of West Bolangitan, North Bolaang Mongondow Regency.The research used a qualitative approach method. The performance of the communityempowerment program is seen from the five indicators or dimensions of the performance of theempowerment program from UNICEF, namely: welfare, access, critical awareness, participation, andcontrol. The research informants were three village heads and six community members in the threeresearch villages. Data collection using interview guidelines, while the analysis technique used isinteractive model analysis.Based on the results of the study, conclusions were drawn: (1) The dimension of "welfare" isquite good; it means that community empowerment programs provide benefits/contributions to improvingcommunity welfare, but they are not optimal yet. (2) The dimension of â€œaccessâ€ is quite good; it meansthat community empowerment programs contribute/benefit to increasing equality in access to resourcessuch as information, business skills training, ease of obtaining small business credit, but not optimal yet.(3) The dimension of â€œcritical awarenessâ€ is quite good; it means that village community empowermentprograms can increase public awareness of the importance of improving welfare, but it is not optimal. (4)The dimension of â€œparticipationâ€ is quite good; it means that the village community empowermentprogram can increase community participation in village institutions, and participation in villagedevelopment, but it is not optimal. (5) The â€œcontrolâ€ dimension is good enough; This means thatcommunity empowerment programs can improve the ability of rural communities to control and managetheir resources, but they are not optimal.Keywords: Community Empowerment, Empowerment Program Performance.